14.7k views
3 votes
Need help asap need it thenext few minutes

Need help asap need it thenext few minutes-example-1
User Fried Rice
by
5.0k points

1 Answer

4 votes

Answer:

Correct Option is d
(x+3)^2 = 11

Explanation:

For completing the square our equation should be in the form of
a^2 +2ab + b^2 = (a+b)^2

In the given equation we have:


x^2 +6x -2\\x^2 + 2(x) (?) +(?)^2 = 2\\for\,\, making\,\, 6x\,\, 2*x*3=6x \\so, \,\,we\,\, can\,\, add\,\, and\,\, subtract\,\, (3)^2 \,\,on\,\, both\,\, sides\\x^2 + 2(x) (3) +(3)^2 -(3)^2= 2\\(x+3)^2 -9 =2\\(x+3)^2 =2+9\\(x+3)^2 = 11

Correct Option is d
(x+3)^2 = 11

User HourGlass
by
5.2k points